The Design of Capacitive Slit on Improving the Antenna Gain of Binomial Double Strip Hexacula Omnidirectional Broadband Antenna - Syahrial Syahrial; Safwan Safwan; Rizal Munadi; Roslidar Roslidar (Universitas Ahmad Dahlan, 2018)
The capacitive slit is a method of making the impedance value to be resistive. To achieve this goal is a challenge in addition to the slit antenna and gives impact to gain as one of the important parameters in antenna design. The antenna gain in a particular direction is defined as 4π times the ratio of radiation intensity in that direction to the power received by the transmitter antenna. In this research, the proposed capacitive slit method was tested on the hexacula omnidirectional broadband antenna operating on frequency 0.85-3 GHz and gain 4.8 dBi. The testing was conducted to obtain the gain improvement of the hexacula omnidirectional broadband antenna. The placement of the capacitive slit was implemented on double strip antenna with 4 times experiments. The best experiment result was obtained when three capacitive slits were placed on different strips. The capacitive slit was designed by analyzing the average value of input impedance before calculating the dimension of the capacitive slit that applied to the antenna. The experiment result shows that the best value of antenna gain is 7.19 dBi. The gain increment is linear to the number of capacitive slits applied to the antenna.